Komitmen Dosen dan Kesejahteraan: Peran Manajemen Dalam Menciptakan Lingkungan Kerja Yang Produktif - Julianto, Pebi (PT. Alahyan Publisher Sukabumi, 2024)
Faculty commitment and well-being are crucial factors for the success and sustainability of higher education institutions. Effective management plays a vital role in enhancing these aspects, ensuring that faculty remain motivated, satisfied, and productive. This study explores the complex relationship between faculty commitment, well-being, and management practices. By understanding how management strategies influence faculty well-being, we can cultivate an environment that supports personal and professional growth, thereby increasing institutional commitment and effectiveness overall. Good management not only provides adequate facilities and resources but also fosters an inclusive and collaborative work culture. In the context of higher education, effective management can enhance faculty well-being, thereby strengthening their commitment to the institution. This is essential for achieving long-term academic vision and mission, as well as promoting overall job satisfaction and productivity among faculty.